Based on "Computer Internet +" Rural Homestay Tourism Product Marketing. (20th July 2022) - Lu, Fangfang; Hu, Mingfang; Zhou, Wusheng; Wang, Kelly Yujie
Abstract : With the development of the Internet and the strong support of national policies, network technology has been widely used in all fields, and the way of information release is not only faster but also more extensive. With the strong support of the state, network technology has been widely used in all areas of society, and the number of Internet users is also increasing, and rural homestay tourism is a new force in the development of rural tourism. Rural homestay tourism plays a unique role in rural employment increase, active industry, active environment, active culture, and other aspects, so more measures should be taken to promote the development of rural homestay tourism. Therefore, by combining the above two points, rural homestay tourism also needs to carry out practical changes. The combination of Internet and rural tourism marketing is a new marketing mode, which opens up a new way for rural tourism product marketing innovation. Due to the huge market demand and various policy support at the national level, the homestay industry has become a breakthrough point for local activation. The author conducted a survey on the situation of "Internet +" rural tourism, guided and analyzed the results, found out the problems existing in the Internet marketing of rural tourism products, and put forward the strategies to deal with the Internet marketing of rural tourism products.